Comparison of new flexible pavement design according to the AASHTO 93 design method, current Chilean regulations, and the NCHRP 1-37A mechanistic-empirical pavement design guide - Wahr Daniel, Carlos (2025)
This research presents a new flexible pavement designs comparison between the design method presented in AASHTO 93, the valid regulations currently in Chile and the Empirical-Mechanistic Pavements Design Guide NCHRP 1-37A. This work was made for pavements of Valparaíso Region, Chile.  The NCHRP 1-37A design guide introduced a new concept for the traffic data: the load normalized spectrum by axles in replacement of the equivalent axles. To obtain this new variable is necessary to apply the proposed guide methodology, using the information of fixed weigh located in the Metropolitan Region. The variable associate to climate is incorporated to the design through the use of weather stations that are adjusted to the study region, created from temperature data, wind velocity, cloudiness, rainfall and relative humidity. Regarding to the pavement structure, this research choose designs that comply with the national specifications and based on asphalt mixtures properties it develope Master Curves, according to the Level 2 of the Empirical-Mechanistic Pavements Design Guide NCHRP 1-37A. To do these characterization, were employed six asphalt binders CA 60/80 from the main asphalt industries of the country and five asphalt mixtures designs actually employed.  From the results obtained by three programs, as a summary, is dear that the structure does not vary substantially, although it is a difference between the designs based on AASHTO 93 and PAVIVIAL: these do not estimate distress development, contrasting with the predictions obtained by the Empirical-Mechanistic Pavements Design Guide NCHRP 1-37A It's important to emphasize that in the empirical-mechanistic procedure the distress models have not been calibrated for the national realty. which impacts in the results obtained in this study.